PERMAINAN ANAK MASA KINI DAN KONTRIBUSINYA PADA PENDIDIKAN KARAKTER ANAK - Arif Sofianto (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2016)
Game for children could be an important tools for character education. However, rapid advances in technology have influenced the development of games for children. Technology have positive and negative impacts on children. The purposes of this study were: 1) to identify types of games for children nowadays, and 2) to analyze the role of games for children in building children’s character. This is a qualitative descriptive research, with spradley’s analysis model. The research was conducted in Semarang Municipal and Semarang Regency. This study concluded that; 1) the growing numbers of games for children today is dominated by modern games such as video games, sport games, and other games that aim to give pleasure. Meanwhile, traditional and educational games are rare. 2) The role of games for children in shaping character of children could be divided in two, namely postive and negative. In the positive side, games for children could increase intelligence, creativity, perception, progressive attitude, high imagination about the future, and widespread knowledge of life. While in the negative side, children could be less friendly, closed, less honest, selfish, less responsible, and does not really like togetherness, which is then making them more selfish and closed